Comparing journalistic cultures : constructing the identity of Fred van der Vyver as newsmaker - Le Roux, Judie (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2009.